2009
DOI: 10.1177/1076029609338044
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of the Biological Activity of 2 Formulations of Enoxaparin in 12 Healthy Volunteers

Abstract: After a single-dose injection in healthy participants, anti-Xa activities of 2 formulations of LMWH enoxaparin were comparable. No significant difference was observed in the mean plasma aPTT. It remains to be seen whether the 2 formulations would show comparable clinical efficacy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…Several recent pharmacodynamic investigations [28][29][30] reinforce the earlier recommendation of the Working Party of the SSC on Control of Anticoagulation of the ISTH [6] that Phase I clinical trials in human volunteers should be performed using a low prophylactic and a high therapeutic dose over 5-7 days each (Table S1). …”
Section: Recommendationmentioning
confidence: 69%
See 1 more Smart Citation
“…Several recent pharmacodynamic investigations [28][29][30] reinforce the earlier recommendation of the Working Party of the SSC on Control of Anticoagulation of the ISTH [6] that Phase I clinical trials in human volunteers should be performed using a low prophylactic and a high therapeutic dose over 5-7 days each (Table S1). …”
Section: Recommendationmentioning
confidence: 69%
“…In vitro studies have identified differing strength of activity for biological effects on various coagulation parameters between the originator and the biosimilar versions of LMWHs . In contrast, when only simple anti‐FXa and anti‐FIIa activities were evaluated no differences in activities were found .…”
Section: Pharmacological Characterization Of Originator Vs Biosimilamentioning
confidence: 99%
“…The FDA approved the first copy of enoxaparin in 2010, using the expedited Abbreviated New Drug Application procedure proposed for requests for marketing authorization of small-molecule chemical drugs [3]. Several copies of enoxaparin are currently available worldwide and appeared in several countries such as China, India and Brazil [3][4][5]. Enoxamed ® is the second copy of enoxaparin approved in Tunisia [16].…”
Section: Discussionmentioning
confidence: 99%
“…Otherwise, enoxaparin experienced generic competition starting in 2010 [3]. In fact, generic versions of enoxaparin are available for clinical use in several countries [4,5]. However, the manufacturing process for biologics is complex which makes difficult to obtain exact replicas of the reference biologic.…”
Section: Introductionmentioning
confidence: 99%
“…In the last decade, patent rights and supplementary protection certificates of branded enoxaparin have expired raising the opportunity to develop copies of this innovator product. As a consequence, generic enoxaparin appeared on the market in many countries such as China, India and Brazil [6][7][8]. Similarly, a new generic enoxaparin was recently proposed in Tunisia.…”
Section: Introductionmentioning
confidence: 99%